REAKSI PASAR TERHADAP PUBLIKASI ANNUAL REPORT AWARD - Citra Kemala, Kadek; Agung Ulupui, I Gusti Ketut (E-Jurnal Akuntansi, 2015)
This research was conducted to examine the market reaction to the publication of the Annual Report Award (ARA). Market reaction can be seen from the difference in abnormal returns before and after the publication. This research was conducted at the company who won the award in ARA 2012, samples used in this study were 11 companies. Data research using secondary data, the data is the closing stock price of each company during the event window, with the 5 day before, during and 5 days after publication. Expected return calculated using the market adjusted model and hypotheses were tested using paired sample t-test. Test results showed that the publication of the Annual Report Award (ARA) in 2012 was not responded by the market with no significant abnormal returns before and after publication. This suggests that the publication of ARA 2012 does not have the information content that able to change the investors' decision to invest.
Keywords: annual report award, abnormal return, good corporate governance, event study